Perancangan Mikrotik untuk Jaringan Hotspot dengan Sistem Voucher pada PT Elmecon Multikencana - Ade Julian; Hendra Supendar; Riza Fahlapi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
MikroTik RouterOS is a Linux-based operating system that is intended as a network router. Designed to suit all users. MAC address-based authentication systems may not be able to cope with the significant growth in the number of users. Using different system in a hotspot network can provide additional security advantages. By replacing the MAC address authentication method with a different system, access risks can be reduced to improve overall network security. After the hotspot network with the voucher system is running well, the Company can develop further by adding additional features or services according to the needs of the company. This development can improve security or increase network capacity to accommodate companies. Replacing the system with a Hotspot Voucher system using Mikrotik will increase flexibility, management, and access control in a hotspot network using Mikrotik Router devices, Switches, UTP Cables, and Access points. From the specifications above, Mikrotik is quite suitable for hotspot vouchers with a voucher system to provide flexibility in managing user access. Previously used MAC address-based authentication was difficult to manage and inflexible. With a different system, setting up and managing access becomes more efficient and can be done more easily. Hotspot voucher configuration with a limit of 5 Mbps Download and 5 Mbps Upload. MAC address system can be overcome with a hotspot voucher system. Enterprises can handle significant user growth without compromising access control.